Molecular Characterization and Diversity Analysis for Leaf Folder Resistancein Rice Using Microsatellite Markers - Rao, P. Venkata Ramana; Divyasri, S.; Bhanu, K. Vasanta; Kumari, P. Naga; Karteek, J.; Rani, M. Girija; Kumar, B.N.V.S.R. Ravi; Chamundeswari, N.; Mohanvishnuvardhan, K.; Roja, V.; et al. (International Journal of Economic Plants, 2016)
Rice is the staple food for more than one half of the world’s population. The major reason for dismal state of rice production and productivity worldwide is due to biotic and abiotic stresses. Among insect pests, rice leaf folder (Cnapholocrocis medinais) earlier considered as a minor pest has gained the status of major pest with the widespread cultivation of HYV and the accompanying changes in cultural practices. Lack of reliable resistant donors is forcing the farmers to depend on insecticides to combat the pest. So, there is an urgent need to identify resistant donors and develop resistant varieties against leaf folder. The present study was carried out to study the extent of variability and molecular genetic diversity for leaf folder resistance in 30 genotypes including susceptible check TN1 under natural conditions. Based on the mean damage score (25, 50 and 75 DAT), 21 genotypes were resistant, 8 were moderately resistant and TN1 was susceptible. Correlation studies among different traits revealed that the trait damage score recorded significant positive correlation with leaf width (r= 0.180**) and SPAD chlorophyll meter reading (r= 0.136**) and non significant negative correlation with leaf length. To study the molecular diversity, 60 microsatellite markers were utilized. UPGMA analysis using NTSYS software grouped the 30 rice genotypes in to three clusters (Cluster I – 1genotype, Cluster II- 11 genotypes and Cluster III – 18 genotypes). UPGMA analysis using Darwin software grouped the 30 rice genotypes in to four clusters (Cluster I – 11 genotypes, Cluster II- 2 genotypes, Cluster III- 7 genotypes and Cluster IV – 10 genotypes). Based on the results it can be concluded that large variability exists in genotypes for leaf folder resistance which can be utilized in breeding programmes to develop rice varieties with resistance to leaf folder coupled with good grain quality and higher yield.